2005
DOI: 10.1101/sqb.2005.70.040
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Pancreatic Cancer in Humans and Mice

Abstract: Animal models of cognate human conditions permit the rigorous exploration of mechanisms of disease pathogenesis and provide systems to devise and test therapeutic and detection strategies. Although inbred mouse strains offer many advantages over other animals for investigations of malignant disease, mice unfortunately do not develop PDA spontaneously or even following carcinogen treatment. Recent technological developments in conditional gene targeting have enabled the generation of mutant mouse cancer models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…9). Recent studies have demonstrated that KRAS is capable of inducing autophagy in cancer cells through an increase in reactive oxygen species (10,(21)(22)(23). The increase in intracellular reactive oxygen species induced by oncogenic KRAS activates JNK and promotes autophagy and the expression of ATG5 and ATG7, which are components of the autophagosome (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). Recent studies have demonstrated that KRAS is capable of inducing autophagy in cancer cells through an increase in reactive oxygen species (10,(21)(22)(23). The increase in intracellular reactive oxygen species induced by oncogenic KRAS activates JNK and promotes autophagy and the expression of ATG5 and ATG7, which are components of the autophagosome (21).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic Mice-krasG12D Cre transgenic mice and their corresponding wild-type littermates were kindly provided by Dr. Fergus Couch (Mayo Clinic, Rochester, MN), as described previously (21,27). The recombined krasG12D allele was identified by PCR using the primer sets described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…T reg suppression assays were done in triplicate in 96-well, flat-bottom plates. (24,27). Both the number and grade of PanIN lesions increase with age, and the mice ultimately develop invasive PDA, frequently accompanied by metastases to the lung, liver, and elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The early stage of the disease is characterized by pancreatic intraepithelial neoplasia lesions (PanIN) bearing mutations in the Kras proto-oncogene, which progress to malignant PDAC by accumulating mutations in other pathways, most frequently in the tumor suppressor genes p16-Ink4A, Trp53, and Smad4 (Tuveson and Hingorani 2005;Bardeesy et al 2006a;Hezel et al 2006). Knowledge of the mutations that occur frequently in human patients has guided the engineering of a new generation of mouse models of PDAC that recapitulate more faithfully the pathology of the human disease (Aguirre et al 2003;Hingorani et al 2003), and in which the contribution of other signaling pathways to PDAC tumorigenesis can be assessed.…”
mentioning
confidence: 99%